Schengen Area and Mass Migrations: The End of a Dream? - Staničić, Frane (Migration and Central Europe: Challenges and Legal Responses, 2024)
The idea of Schengen as a vast area without (inner) borders has been active since 1984. For a long time, the idea of a “borderless Europe” thrived because external borders of the Schengen area were adequately protected. However, after 2005, when it was said that Schengen had come to epitomise freedom, security, and European success, the first cracks in the mutual trust among the Member States began appearing and became obvious in 2011 during the French-Italian row when France introduced border controls with Italy. The migrant crisis in 2015 with the reintroduction of numerous (and long lasting) inner border controls showed how the Schengen area is in reality fragile. This chapter deals with the current situation in the Schengen area and tries to show whether Schengen can survive as an undisputedly important achievement in the process of Europeanisation. However, while coping with the shortcomings of Schengen and establishing stronger and more efficient controls on the external border, protection of individual human rights must not be neglected. Keywords: Schengen, Schengen Border Code, migrations, border controls, human rights.